2016
DOI: 10.1177/0308022616630329
|View full text |Cite
|
Sign up to set email alerts
|

Occupational therapy roles and responsibilities: Evidence from a pilot study of time use in an integrated health and social care trust

Abstract: Introduction: Occupational therapists undertake a broad spectrum of activities, yet no mechanism exists to record how working time is distributed across them. This is a hindrance to research, evaluation and evidence-based practice. Method: A new diary schedule was piloted by 151 qualified and assistant-grade practitioners working in multiple adult health and social care settings in an integrated NHS and social care trust in England. Time use relating to 37 occupational therapy tasks was recorded in 30 minute i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(10 citation statements)
references
References 16 publications
0
10
0
Order By: Relevance
“…This finding was linked to more senior clinicians having more managerial and administrative responsibilities thereby reducing their time available to spend with patients (Evans, ; Hearn, Govier & Semciw, ; Simmons & Kuys, ). In addition, the clinicians’ choice of clinical caseload and its impact on the amount and type of occupational therapy provided was identified as another factor impacting on occupational therapist time‐use (Florian, Sheffer & Sachs, ; Smith, ; Wilberforce et al ., ), which helps to explain differences in time‐use patterns across the range of the included studies.…”
Section: Resultsmentioning
confidence: 99%
“…This finding was linked to more senior clinicians having more managerial and administrative responsibilities thereby reducing their time available to spend with patients (Evans, ; Hearn, Govier & Semciw, ; Simmons & Kuys, ). In addition, the clinicians’ choice of clinical caseload and its impact on the amount and type of occupational therapy provided was identified as another factor impacting on occupational therapist time‐use (Florian, Sheffer & Sachs, ; Smith, ; Wilberforce et al ., ), which helps to explain differences in time‐use patterns across the range of the included studies.…”
Section: Resultsmentioning
confidence: 99%
“…However, in choosing this time frame in this study considerations of the applicability of the diary measure to working lives and the convenience of completion were given priority in the design of the questionnaire to encourage a high response rate. The response rate of 62% in the pilot study suggested that this objective was achieved (Wilberforce et al, 2016). Further sub-division of activities might have increased the possibility of a lower response rate.…”
Section: Methodological Challengesmentioning
confidence: 93%
“…The diary schedule was piloted with a large sample of occupational therapy practitioners in the host trust (Wilberforce et al, 2016). Following this a narrative and pragmatic evaluation of the schedule was undertaken in three parts.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations